Dynamic response of a slender sandwich pipe with a metallic foam core subjected to low-velocity impact. (15th April 2023) - Xiang, Chunping; Wang, Jiao; Chen, Shangjun; Fan, Guoxi
Abstract: The sandwich pipe (SP) is capable of submarine applications to adapt the deepwater harsh environments for the excellent thermal insulation and structural strength. Due to the absence of the yield criterion, the plastic behaviours of the SPs under impact are not well understood despite the structures are threatened by impact from fishing boats, digging equipment, and anchors. In the present paper, a yield criterion considering the effect of core strength was proposed for the SPs, and the dynamic response of a fully clamped slender SP under transverse impact was predicted theoretically by considering the interaction of stretching and bending of the structure. To verify the theoretical predictions, the finite element models were established, and good agreements were achieved between the theoretical predictions and the numerical results. It is demonstrated that the large deflection of SPs is dominated by the axial force. The present work can provide the basic understandings of the structural behaviours of SPs for their safety in submarine applications threated by transverse impact.